2014
DOI: 10.5935/abc.20140155
|View full text |Cite
|
Sign up to set email alerts
|

Association between Angiotensin-Converting Enzyme Inhibitors and Troponin in Acute Coronary Syndrome

Abstract: BackgroundCardiovascular disease is the leading cause of mortality in the western world and its treatment should be optimized to decrease severe adverse events.ObjectiveTo determine the effect of previous use of angiotensin-converting enzyme inhibitors on cardiac troponin I measurement in patients with acute coronary syndrome without ST-segment elevation and evaluate clinical outcomes at 180 days.MethodsProspective, observational study, carried out in a tertiary center, in patients with acute coronary syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(37 reference statements)
0
1
0
2
Order By: Relevance
“…L.Minuzzo et al [11] investigated the effect of previous use of angiotensin-converting enzyme inhibitors on cardiac troponin I measurement in patients with acute coronary syndrome without ST-segment elevation and clinical outcomes at 180 days. This study showed a correlation between prior use of ACEIs and reduction in the myocardial necrosis marker troponin I in patients admitted for acute coronary syndrome without ST-segment elevation.…”
Section: Discussionmentioning
confidence: 99%
“…L.Minuzzo et al [11] investigated the effect of previous use of angiotensin-converting enzyme inhibitors on cardiac troponin I measurement in patients with acute coronary syndrome without ST-segment elevation and clinical outcomes at 180 days. This study showed a correlation between prior use of ACEIs and reduction in the myocardial necrosis marker troponin I in patients admitted for acute coronary syndrome without ST-segment elevation.…”
Section: Discussionmentioning
confidence: 99%
“…O uso mais comum de anti-hipertensivo na farmacoterapia cardiovascular pósinfarto são os antagonistas de receptores de angiotensina I, as evidências clínicas mostram que pacientes pós-infartados melhoraram a função cardíaca e reduziram o reinfarto. Esses efeitos foram atribuídos à diminuição do remodelamento cardíaco em indivíduos com disfunção ventricular esquerda, graças a modulação no sistema renina-angiotensina-aldosterona (MINUZZO et al, 2014;LEE et al, 2016). Adicionalmente, os antagonistas dos receptores para aldosterona, como o eplerone aperfeiçoou o tratamento farmacológico múltiplo aplicado com inibidores da enzima conversora de angiotensina, aspirina, betabloqueador e estatinas, reduzindo 17% a mortalidade de indivíduos pós-infarto em comparação com o grupo placebo com mesmo protocolo farmacoterapêutico (PITT et al, 2003).…”
Section: Estratégias Convencionais Para O Tratamento E Manejo Do Infa...unclassified
“…L. Minuzzo и соавт. показали, что у больных, госпитализированных по поводу ОКСбпST, которым ранее назначались иАПФ, было отмечено снижение уровня маркера некроза миокарда тропонина I, однако данных, подтверждающих, что это снижение может ассоциироваться с меньшим количеством тяжелых клинических исходов, таких как смерть и повторный инфаркт в течение 180 дней, получено не было [29]. β-адреноблокаторы β-адреноблокаторы показаны всем пациентам с ОКС при отсутствии противопоказаний, таких как атриовентрикулярная блокада II и III степени, снижение систолического артериального давления >100 мм рт.…”
Section: блокаторы ренин-ангиотензин-альдостероновой системыunclassified